2008
DOI: 10.3988/jcn.2008.4.2.67
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial Hemodynamic Changes During Adult Moyamoya Disease Progression

Abstract: Background and purpose: This study evaluated the changes in blood flow velocity in the anterior and posterior intracranial circulations according to the progression of moyamoya disease in adult patients.Methods: We evaluated Suzuki's angiographic stage and mean blood flow velocity (MBFV) changes in intracranial vessels from both sides in 19 adult moyamoya patients. We then analyzed the linearity of MBFV changes from early to late moyamoya stages in each intracranial vessel using piecewise linear regression mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 16 publications
1
14
0
Order By: Relevance
“…Leptomeningeal collaterals from the posterior cerebral artery (PCA), which were scant during the early stages of MMD, develop prominently as the stage progresses 3. However, as the stages of MMD advance further, these collaterals decrease significantly 11. The honeycomb pattern of infarctions is known to appear in these advanced PCA stages,3 which was also demonstrated in this study.…”
Section: Discussionsupporting
confidence: 82%
“…Leptomeningeal collaterals from the posterior cerebral artery (PCA), which were scant during the early stages of MMD, develop prominently as the stage progresses 3. However, as the stages of MMD advance further, these collaterals decrease significantly 11. The honeycomb pattern of infarctions is known to appear in these advanced PCA stages,3 which was also demonstrated in this study.…”
Section: Discussionsupporting
confidence: 82%
“…To the best of our knowledge, only a few studies have investigated MCA flow velocity in patients with MMD. 13,14,19 These studies have shown that the MFV in the MCA peaks at Suzuki Stage II or III and decreases with more advanced stages. Our data showed similar findings for advanced-stage (Suzuki Stage IV or V) MMDs, but high MFV peaked at an earlier MMD stage (i.e., Suzuki Stage I).…”
Section: None Of the 2 Patients Had A Postrevascularization Infarctionmentioning
confidence: 96%
“…However, once baseline data are procured for each patient, flow velocities can be followed in real time for progressive stenosis and worsening perfusion. 68,69 In the postoperative period for these children, serial transcranial Doppler sonography may identify worsening cerebral perfusion from a TIA or an ischemic stroke, hyperperfusion, or vasospasm. These different flow profiles may lead to alternative strategies for BP, ventilation, and fluid management in this cohort.…”
Section: Stroke and Cerebrovascular Disordersmentioning
confidence: 99%